ERVING GOFFMAN, AS INTERAÇÕES NO COTIDIANO ESCOLAR, DESVENDANDO O ESTIGMA DENTRO DA INCLUSÃO ESCOLAR - Nascimento, Manoel Alves do (2009)
People with disabilities are excluded from society because of the negative mark of discrediting received by the social environment - for his appearance or his way of being different - that puts out the standard classifying them as being deviant. In everyday school say whether these brands and they reproduce, not encouraging people with disabilities overcome such a stigma. The research aims to examine how stigma built by students with disabilities influence the process of interaction and inclusion school, studying evidence as it develops the process of stigmatization in the light of school everyday thoughts of Erving Goffman. It is used a literature review of the specific theme, based on studies of Erving Goffman together the empirical research based on the ethnographic experienced by the author in his studies of community, is used as strategies for research, interviews with teachers and 3 comments recorded scenes of daily life through school, 2 public schools in Brazil. In chapter.1 we seek to understand the constructs of Goffman mainly through his academic career in chapter.2 the work focused on understanding the social interaction and mainly defined by the author in question as an order of interaction, where people are authors within of a social scene in chapter 3. the research revolves around the end stigma and how this influences the interaction and the advancement of people with disabilities, finally finishes the work in chapter .4 presenting the analysis of records of interviews and scenes of everyday school life. The selected scenes show the actors involved, the scenario, and the plot of the interactions, identifying the strategies of stigma built by students with disabilities, seeking connections with the inclusive policies and the Brazilian schools. First comes the research identifying the school as a means of socialization and creation of knowledge has an important role in this process of change, although often play the social stigma. The school can help in changing the look that excludes, unmasking some of the masks and own social inclusion; their renewal and their stakeholders should value the differences in construction of new knowledge(AU)